2019
DOI: 10.6018/analesps.35.2.336941
|View full text |Cite
|
Sign up to set email alerts
|

Coping strategies and self-esteem in women with breast cancer

Abstract: Título: Estrategias de afrontamiento y autoestima en mujeres con cáncer de mama. Resumen: El afrontamiento del diagnóstico de cáncer de mama y el uso de diferentes estrategias es clave para superar esta situación estresante. Diversas variables psicológicas están relacionadas con la manera de afrontar la enfermedad, destacando entre ellas la autoestima. Se analiza la influencia que la edad, de las pacientes con cáncer de mama, pueda tener en las estrategias de afrontamiento ante la enfermedad, analizando si la … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 38 publications
1
9
1
4
Order By: Relevance
“…Social support also appears to be strongly related to self-esteem, in line with the sociometer theory, which postulates that selfesteem is an indicator of social inclusion (Leary and Baumeister, 2000). The relationship between social support and self-esteem has been widely studied in cancer patients (Curbow and Somerfield, 1991;Schroevers et al, 2003b;Mingorance et al, 2019;Pardede et al, 2020), and appears to be of prime importance. In particular, it has been shown that positive relationships with others are more strongly correlated with the level of self-esteem in female cancer patients than in age-matched healthy women (Carpenter, 1998).…”
Section: Self-esteem As a Psychological Resource In Cancersupporting
confidence: 61%
See 1 more Smart Citation
“…Social support also appears to be strongly related to self-esteem, in line with the sociometer theory, which postulates that selfesteem is an indicator of social inclusion (Leary and Baumeister, 2000). The relationship between social support and self-esteem has been widely studied in cancer patients (Curbow and Somerfield, 1991;Schroevers et al, 2003b;Mingorance et al, 2019;Pardede et al, 2020), and appears to be of prime importance. In particular, it has been shown that positive relationships with others are more strongly correlated with the level of self-esteem in female cancer patients than in age-matched healthy women (Carpenter, 1998).…”
Section: Self-esteem As a Psychological Resource In Cancersupporting
confidence: 61%
“…Cieślak and Golusiński (2018) showed that greater acceptance of cancer-related disability was associated with high self-esteem. Mingorance et al (2019) also identified that adaptive adjustment strategies (positive reframing, use of emotional support, active coping, acceptance, and planning) in breast cancer patients were associated with high self-esteem. Social support also appears to be strongly related to self-esteem, in line with the sociometer theory, which postulates that selfesteem is an indicator of social inclusion (Leary and Baumeister, 2000).…”
Section: Self-esteem As a Psychological Resource In Cancermentioning
confidence: 93%
“…One of the major limitations is represented by the shortness of the assessment protocol administered. Indeed it should be also noted that, differently from previous literature [ 7 , 20 , 64 , 65 ], our results highlighted that patients’ age and the type of surgery could predict neither growth, nor drop, in patients’ perceived distress. This difference could be explained in light of the brief timespan occurring between pre- and post-surgery assessments in our study.…”
Section: Discussioncontrasting
confidence: 99%
“…Breast cancer was the most prevalent (11), followed by cervical and endometrial cancer, which accounted for the greater participation of the female gender in this study; regarding the male gender, the types of cancer with the greatest presentation were prostate and head and neck cancers. In both sexes, stages II and III were prevalent, while the effects of treatment were significantly more common in adults who received radiotherapy (12).…”
Section: Discussionmentioning
confidence: 99%